Photodynamic Antimicrobial Action of Asymmetrical Porphyrins Functionalized Silver-Detonation Nanodiamonds Nanoplatforms for the Suppression of Staphylococcus aureus Planktonic Cells and Biofilms - Openda, Yolande I.; Ngoy, Bokolombe P.; Nyokong, Tebello (Frontiers in Chemistry, 2021)
New asymmetrical porphyrin derivatives containing a p-hydroxyphenyl moiety and p-acetylphenyl moieties along with their functionalized silver-detonation nanodiamonds nanohybrids were characterized and their photophysicochemical properties were established. The study provides evidence that the metalated porphyrin derivatives were red-shifted in absorption wavelength and possessed high singlet oxygen quantum yield comparative to the unmetalated core, thus making them suitable agents for photodynamic antimicrobial chemotherapy. As a result of conjugation to detonation nanodiamonds and silver nanoparticles, these compounds proved to be more effective as they exhibited stronger antibacterial and anti-biofilm activities on the multi-drug resistant S. aureus strain due to synergetic effect, compared to Ps alone. This suggests that the newly prepared nanohybrids could be used as a potential antimicrobial agent in the treatment of biofilms caused by S. aureus strain.